Understanding of black salve toxicity by multi-compound cytotoxicity assays - Andrew Croaker; Arie Davis; Anthony Carroll; Lei Liu; Stephen P. Myers (BMC, 2022)
Abstract Background Black salve is a controversial complementary and alternative medicine (CAM) associated with skin toxicity and skin cancer treatment failures. Black salve formulations vary between manufacturers and contain a number of botanical and synthetic constituents. The skin cancer cytotoxicity of a number of these constituents has not been assessed to date. The alkaloids from the rhizomes of Sanguinaria canadensis, a key black salve ingredient, have had their single compound cytotoxicity assessed; however, whether they possess synergistic cytotoxicity with other compounds has not been studied and is of direct clinical relevance. This research aimed to improve our understanding of the skin cancer cytotoxicity of black salve constituents. Methods The cytotoxicity of individual and combination black salve constituents were assessed against the A375 melanoma and A431 squamous cell carcinoma cell lines. Cytotoxicity was determined using the Resazurin assay with fluorescence measured using a Tecan Infinite 200 Pro Microplate reader, compound cytotoxicity being compared to that of the topical cancer therapeutic agent, 5- fluouracil. Docetaxal was used as a positive control. Dunnetts p value was used to determine whether significant synergistic cytotoxicity was present. Results Sanguinarine was the most cytotoxic compound tested with a 24-hour IC50 of 2.1 μM against the A375 Melanoma cell line and 3.14 μM against the A431 SCC cell line. All black salve constituents showed greater cytotoxicity against the two skin cancer cell lines tested than the skin cancer therapeutic 5-Fluouracil with 24 hours of compound exposure. Chelerythrine and minor Quaternary Benzophenanthridine Alkaloids (QBAs) present in black salve, at concentrations not having a cytotoxic effect by themselves, boosted the cytotoxic effects of sanguinarine. This could be a synergistic rather than additive cytotoxic effect although the synergistic effect was cell line and concentration dependent. Conclusions Black salve contains several cytotoxic compounds, a number of which have been found to possess synergistic cytotoxicity for the first time against skin cancer cell lines. In addition, these compounds together increase the overall cytotoxic effect. Assessing multi-compound cytotoxicity in herbal medicine can provide additional information about both their therapeutic and toxicity potential. As black salve is currently being used by patients, further cytotoxicity work should be undertaken to assess whether synergistic cytotoxicity exists when tested in normal skin cells.